The Influence of Precipitation and Consecutive Dry Days on Burned Areas in Yunnan Province, Southwestern China - Feng Chen; Zhaofei Fan; Shukui Niu; Jingming Zheng (Advances in Meteorology)
Precipitation is among the more limiting meteorological factors affecting the occurrence and extent of forest fire. We examined the correlation between burned area of individual wildfires and the rainfall amounts occurring on the day of the burn and the number of consecutive dry days for a range of limiting daily rainfall amounts (0–6mm) used to define a “dry” day. Daily threshold rainfall levels that most significantly affected area burned were determined for each ecoregion in Yunnan province, a major fire-prone area, in southwestern China. Results showed that the burned area of a wildfire decreased exponentially with increasing rainfall amounts on the day of burning. Burned area was also positively correlated to the number of consecutive dry days prior to burning. The threshold rainfall value providing the highest correlation between burned area and the number of consecutive dry days prior to a burn varied between ecoregions. Consecutive dry days with rainfall less than the specified threshold predominantly affected large fires (>100 ha) rather than more frequently occurring small fires. These results will help forest managers evaluate regionalfire danger indices for forest fire prevention, particularly for catastrophic forest wildfires causing significant economic losses and threats to human life and environment.